Incremental Effectiveness of Emergency Vaccination Against a Varicella Outbreak at an Elementary School in Beijing, China, 2019: An Observational Cohort Study - Zhiqiang Cao; Dan Zhao; Rujing Shi; Yanhong Zhao; Xiaojing Wen; Ying Ma; Xiaomei Li; Luodan Suo (Vaccines, 2024)
(1) Background: The effect of varicella emergency vaccination (EV) has not been fully evaluated. (2) Methods: This was a cohort study. Participants were categorized into five groups based on their immune status: unvaccinated group, first dose as EV group, one dose no EV group, second dose as EV group, and two doses no EV group. A Cox proportional hazards model was employed to examine the association between the EV measures and the varicella incidence rate in this outbreak. (3) Results: Demographic characteristics, vaccination details, and disease onset information were 100% (918/918) collected. The crude attack rate was 44% (11/25), 8% (3/36), 11% (24/215), 3% (6/176), and 2% (8/466) among the unvaccinated group, first dose as EV group, one dose no EV group, second dose as EV group and two doses no EV group, respectively. Compared to the unvaccinated group and the one dose no EV group, the first dose varicella vaccine as EV and the second dose as EV demonstrated an incremental effectiveness of 90% (95% CI 65–97%) and 79% (95% CI 47–92%), respectively. (4) Conclusions: Both the first dose and the second dose as EV contributed to reducing the incidence rates of varicella and offered incremental vaccine effectiveness in an outbreak setting. Our study underscores the importance and benefits of initiating emergency varicella vaccination early to reduce the disease incidence rate in an elementary school setting where there was no complete coverage of the two doses of varicella vaccine and an outbreak occurred.